Challenges and Constraints in Adopting Modern Horticulture Practices in Apple Orchards - Thakur, Jyoti; Pandey, Uma (Journal of Extension Education, 2025)
In many developing countries the adoption rate of new agricultural technology especially by small-scale farmers is low. The factors influencing farmers’ adoption of new technologies vary from specific circumstances to local conditions. The most essential aspect in the adoption of new tools and techniques is the farmer’s perception of these technologies which often remains unidentified. Using a mixed method approach, this study explored marginal and small-scale apple orchardists of rural Shimla in Himachal Pradesh, India for their perceptions, challenges, and limitations of adaptive capacity to modern horticulture practices. Via in-depth interviews, the growers shared multifaceted challenges and fears impeding their adoption decision, the most noticeable ones were - the high cost of horticulture inputs, unpredictable weather conditions, small orchard size, inadequate labour, insufficient knowledge on modern horticulture practices and lack of information from the government departments. Based on these interviews, a thematic analysis and a survey were conducted - broadly representing the common horticulture problems and factors restricting these orchardists from adopting new technologies.